2005
DOI: 10.1111/j.1464-410x.2005.05809.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study comparing three‐dimensional computed tomography and magnetic resonance imaging for evaluating the renal vascular anatomy in potential living renal donors

Abstract: left laparoscopic donor nephrectomy (LDN), whereas seven had right open donor nephrectomy (ODN); LDN was only considered if the renal vascular anatomy was favourable on the left. CTA and MRA images were analysed by two radiologists independently. The radiological and surgical findings were correlated after the surgery. RESULTSCTA showed 33 arteries and 32 veins (100% sensitivity) whereas MRA showed 32 arteries and 31 veins (97% sensitivity). CTA detected all five accessory renal arteries whereas MRA only detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…As stated by Shih and Hagspiel, no direct comparison of MRA and CTA for mesenteric artery stenosis has been published [6], and as there is no comparison of all three noninvasive modalities versus DSA as the reference standard available in the literature, our study offers the first comprehensive comparative results for all modalities in the evaluation of mesenteric artery stenosis. Corresponding to Bhatti et al [12] who found CTA superior to MRA in renal arteries, our data indicate the superiority of CTA over MRA and duplex US in the two mesenteric arteries. Loewe et al refer to the outstanding role of CTA as a safe, robust and reproducible modality for diagnosing diseased abdominal arteries, and they rated the broad majority of their evaluated abdominal arteries as of good or excellent image quality [13].…”
Section: Image Qualitysupporting
confidence: 59%
“…As stated by Shih and Hagspiel, no direct comparison of MRA and CTA for mesenteric artery stenosis has been published [6], and as there is no comparison of all three noninvasive modalities versus DSA as the reference standard available in the literature, our study offers the first comprehensive comparative results for all modalities in the evaluation of mesenteric artery stenosis. Corresponding to Bhatti et al [12] who found CTA superior to MRA in renal arteries, our data indicate the superiority of CTA over MRA and duplex US in the two mesenteric arteries. Loewe et al refer to the outstanding role of CTA as a safe, robust and reproducible modality for diagnosing diseased abdominal arteries, and they rated the broad majority of their evaluated abdominal arteries as of good or excellent image quality [13].…”
Section: Image Qualitysupporting
confidence: 59%
“…Findings have shown CT to be more accurate than magnetic resonance angiography in detecting renal arterial and venous anomalies [8]. In our study, 16% of the donor organs had multiple arteries.…”
Section: Discussionmentioning
confidence: 75%
“…There has been debate as to the most appropriate method for demonstrating the renal vascular anatomy in potential renal donors [5,7,[25][26][27], but there is increasing evidence to support the sole use of CE MRA as a suitable method [4,6,9,[28][29][30]. However, the use of any contrast medium carries a potential risk and, in the case of gadolinium-based media, nephrotoxicity and allergic reactions can result [31,32], although they are infrequent and usually mild.…”
Section: Discussionmentioning
confidence: 99%